2020
DOI: 10.1093/jas/skaa392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of feeding thermally peroxidized lipids on growth performance, lipid digestibility, and oxidative status in nursery pigs

Abstract: Three experiments were conducted to evaluate oil source and peroxidation status (experiment 1) or peroxidized soybean oil (SO; experiments 2 and 3) on growth performance, oxidative stress, and digestibility of dietary ether extract (EE). In experiment 1, palm oil (PO), poultry fat (PF), canola oil (CO), and SO were evaluated, while in experiments 2 and 3, only SO was evaluated. Lipids were either an unheated control (CNT) or thermally processed at 90 °C for 72 hr, being added at 10%, 7.5%, or 3% of the diet in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
1
2
0
Order By: Relevance
“…The calculated peroxide values of the SBO diets and CWG diets fed in the current study were 0.48 and 0.99 mg/kg diet, respectively (data not presented). These peroxide values for diets fed in the current study were within the range of values that were reported by Kerr et al (2020), implying that the performance of pigs in The IDF has an ability to increase feed intake and digestive capacity of GIT by reducing intestinal stasis and increasing activity of digestive enzyme (Molist et al, 2014). Inclusion of SBP in diets for weaned pigs did not affect activity of digestive enzymes in the small intestine (Lizardo et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The calculated peroxide values of the SBO diets and CWG diets fed in the current study were 0.48 and 0.99 mg/kg diet, respectively (data not presented). These peroxide values for diets fed in the current study were within the range of values that were reported by Kerr et al (2020), implying that the performance of pigs in The IDF has an ability to increase feed intake and digestive capacity of GIT by reducing intestinal stasis and increasing activity of digestive enzyme (Molist et al, 2014). Inclusion of SBP in diets for weaned pigs did not affect activity of digestive enzymes in the small intestine (Lizardo et al, 1997).…”
Section: Discussionsupporting
confidence: 84%
“…Peroxide value is the measure of degree of fat rancidity (DeRouchey et al, 2004). Kerr et al (2020) observed that growth performance of pigs fed diet containing peroxidized SBO (with peroxide value of 3.05 mg/kg diet) did not differ from that of pigs fed the control diet (with peroxide value of 0.27 mg/kg diet). The calculated peroxide values of the SBO diets and CWG diets fed in the current study were 0.48 and 0.99 mg/kg diet, respectively (data not presented).…”
Section: Discussionmentioning
confidence: 99%
“…So far, little attention has been paid to human exposure of ROS through food (Nilsson & Liu, 2020), frozen stored fish, for example. Oxidized lipids are also poorly digested (Kerr et al., 2020; Nielson et al., 1985), and they suppress protein digestibility as well (Nielson et al., 1985). Beneficial PUFA for human health (Xu et al., 2020) also decreases in frozen fish over inadequate and longer storage time.…”
Section: Results Of Literature Review and Metadata Analysesmentioning
confidence: 99%